Methotrexate in a psoriatic arthritis patient - K. V. Aleksanyan; E. S. Zholobova; S. N. Chebysheva; A. V. Meleshkina; M. N. Nikolaeva (Сеченовский вестник)
The case report a psoriatic arthritis patient (disﬁguring form, high laboratory values, changes of the skin and nails) treated with methotrexate. The drug demonstrated high eﬃcacy resulting in stable sustained remission of articular syndrome, documented both by clinical and laboratory parameters, decreased cutaneous syndromes, improved functional activity and better life quality.